2011
DOI: 10.1016/j.abb.2011.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Hypochlorite-modified high-density lipoprotein promotes induction of HO-1 in endothelial cells via activation of p42/44 MAPK and zinc finger transcription factor Egr-1

Abstract: Research highlights► Chlorinated HDL promotes expression of heme oxygenase-1 (HO-1) in endothelial cells. ► Expression involves p42/44 MAPK and activation of transcription factor Egr-1. ► EMSA demonstrates induction of Egr-1 DNA binding activity. ► Immunocytochemistry shows translocation of Egr-1 to the nucleus. ► Silencing of p42/44 MAPK and Egr-1 impairs HO-1 expression to baseline levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…It has been shown that miR-199b regulated vascular endothelial growth factor expression and angiogenesis in vivo and functioned as a regulator of the phenotypic switch in vascular cell differentiation by mediating critical signaling angiogenic responses [11]. miR-199b-5p can also regulate proliferation and angiogenesis in mouse myocardial microvascular endothelial cells [23]. Enhanced expression of heme oxygenase-1 in human endothelial cells can be blocked by inhibition of p42/44 MAPK and knockdown of EGR1 [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-199b regulated vascular endothelial growth factor expression and angiogenesis in vivo and functioned as a regulator of the phenotypic switch in vascular cell differentiation by mediating critical signaling angiogenic responses [11]. miR-199b-5p can also regulate proliferation and angiogenesis in mouse myocardial microvascular endothelial cells [23]. Enhanced expression of heme oxygenase-1 in human endothelial cells can be blocked by inhibition of p42/44 MAPK and knockdown of EGR1 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our data fill gaps in the Mox-LDL signal transduction pathway. Ox-LDL have been previously reported to bind to the LOX-1 scavenger receptor and to trigger signal transduction pathways involving several kinases including JNK, pKC, ERK 1 and 2, Raf, and IP3K [ 34 , 45 ]. We focused on the end of this pathway: control of gene expression and phenotypic effects.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main toxic byproduct of MPO is hypochlorous acid, a powerful oxidant that is able to initiate modification of signaling proteins, including transcription factor [76], and to cause tissue dysfunction[77,78] (Figure 2). Interestingly, studies in the literature implicate the neutrophil/MPO axis in adipocyte function, measured as adiponectin abundance.…”
Section: Functional Implication Of P-selectin Upregulationmentioning
confidence: 99%